2015
DOI: 10.11648/j.sjedu.20150304.12
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Mastery Learning and Mind Mapping Approaches in Improving Secondary School Students’ Learning Outcomes in Physics

Abstract: This study investigated the effect of Mastery Learning Approach (MLA) and Mind Mapping Approach (MMA) in improving students' academic performance in Physics and also determined their effect in enhancing students' retention of Physics. These were with a view to ascertaining the best teaching method for improving students' learning outcomes in Physics. The study adopted the non-equivalent pre-test, post-test control group experimental design. Simple random sampling technique was used to select three co-education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
1
1
1
1
Order By: Relevance
“…This finding is similar to that of Bot and Eze (2016) who found that students taught using CM performed better than those taught using a cooperative learning strategy. Similarly, this finding is in line with the earlier finding of Blessing and Olufunke (2015), which showed that students made to learn using CM strategy were better achievers than their counterparts exposed to the mastery learning approach.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is similar to that of Bot and Eze (2016) who found that students taught using CM performed better than those taught using a cooperative learning strategy. Similarly, this finding is in line with the earlier finding of Blessing and Olufunke (2015), which showed that students made to learn using CM strategy were better achievers than their counterparts exposed to the mastery learning approach.…”
Section: Discussionsupporting
confidence: 91%
“…The study findings also showed that students exposed to CM strategy have higher retention capacity than those taught with CML instructional strategy. This finding does not agree with Blessing and Olufunke (2015) whose study found no significant effect of treatment on the retention ability of students taught physics with mastery learning and mind-mapping strategies. Hence, the superiority of CM group over CML group could be as a result of the organization of the concepts in concept map construction.…”
Section: Discussioncontrasting
confidence: 75%
“…Kegiatan yang sangat kompleks melibatkan siswa aktif melakukan pengumpulan data dan membuat mind mapping tidak hanya meningkatkan aktivitas, namun juga pemahaman dan daya ingat siswa. Mencatat dengan menggunakan peta pikiran dapat membuat siswa mudah mengingat dan memahami materi dengan cepat dan luas (Omolara Blessing, 2015). Sejalan dengan pendapat sebelumnya, model pembelajaran yang menyatukan discovery-inquiry berbantuan mind mapping juga membuat siswa memiliki struktur kognitif yang luas dan mampu melihat masalah dari berbagai sudut pandang (Dhindsa, Makarimi-Kasim, & Anderson, 2011).…”
Section: Pembahasanunclassified
“…According to Arredondo & Block (1990), when well implemented separately, both mastery learning and thinking skills programs appear to improve student learning. Although a great deal has been written about how mastery learning and other strategies might be used together extensively to produce positive learning outcomes (Blessing& Olufunke, 2015;Hevedanlı et al, 2002;Krank & Moon, 2001;Laney et al, 1996;Mevarech 1985;Özder 1996;Slavin 1983), there is the apparent lack of combining mastery learning with reflective thinking activities in the literature review.…”
Section: Introductionmentioning
confidence: 99%